Perubahan Budaya Organisasi Melalui Digitalisasi Di SMA Budhi Warman II Jakarta - Faried, Ade Achmad; Adiba; Dara, Satria Danur; Junengsih (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
Digital transformation has become a crucial trend in education, enhancing the effectiveness and efficiency of teaching processes and school management. This qualitative case study explores how digitalization has influenced organizational culture at SMA Budhi Warman II in Jakarta. Through in-depth interviews with teachers and administrative staff, the research reveals that the implementation of digital systems—such as Learning Management Systems (LMS), electronic attendance, and internal communication platforms—has significantly impacted work patterns, collaboration, and organizational values. While digital tools have improved efficiency and transparency, challenges such as technical adaptation, infrastructure limitations, and the need for continuous training have also emerged. The findings indicate that while some staff quickly embrace the changes, others require more time and support to adapt. Overall, the shift toward digital systems has introduced new cultural norms, including technological adaptability, digital discipline, and ethical communication. This study highlights the importance of integrating organizational culture into digital transformation strategies to ensure sustainable and meaningful change in educational institutions.